Immune Response and Histopathological Changes of Serratia rubidaea in Mice - Ikram A.A. Al-Sammarraea (مجلة الانبار للعلوم البيطرية)
Serratia rubidaea is a zoonotic opportunistic pathogen that causes respiratory tract infection, septicemia, and encephalitis in humans and animals. The current study aimed to estimate the immunological response (IgG, IL-6by ELISA test and Delayed Type Hypersensitivity (DTH)-Skin Test and histopathological lesions (intestine, liver, kidney, and spleen) by using twenty-four Swiss mice divided into three equal groups (8/each).The first group(G1) as control negative given PBS (pH 7.2) 0.1ml S/C, the second group(G2) immunized by killed whole cell antigen Serratia rubidaea (KWCA SR) (1.2 ×109CFU ml) S/C and the third group(G3) immunized by sonicated whole cell antigen Serratia rubidaea (SWCASR) (1000 μg/ml) S/C. A booster dose was given after 14 days of immunization to the G2 and G3 the same as the immunizing dose. At 21 and 28 days of immunization, IgG and IL-6 concentrations were increased significantly (P≤0.05) in the groups G2 and G3 compared to the negative control group. DTH-Skin Tests of G2 and G3 groups showed increased induration diameter after 24 and 48 hours. and a decrease at 72 hours. Histopathological lesions showed mild to moderate changes in immunized groups compared with the positive control group in all organs. In conclusion, it was found that KWCASR and SWCASR induce humoral (IgG) and cellular immune responses(IL-6,DTH), which reduce the pathological lesions in the immunized mice. [AJVS 2024; 17(2.000): 17-26]